Natural‐orifice transluminal endoscopic surgery. Issue 2 (January 2015) - Atallah, S.; Martin‐Perez, B.; Keller, D.; Burke, J.; Hunter, L.
<x xml:space="preserve">Abstract</x> Background Natural‐orifice transluminal endoscopic surgery (NOTES) represents one of the most significant innovations in surgery to emerge since the advent of laparoscopy. A decade of progress with this approach has now been catalogued, and yet its clinical application remains controversial. Methods A PubMed search was carried out for articles describing NOTES in both the preclinical and the clinical setting. Public perceptions and expert opinion regarding NOTES in the published literature were analysed carefully. Results Two hundred relevant articles on NOTES were studied and the outcomes reviewed. A division between direct‐ and indirect‐target NOTES was established. The areas with the most promising clinical application included direct‐target NOTES, such as transanal total mesorectal excision and peroral endoscopic myotomy. The clinical experience with distant‐target NOTES, such as for appendicectomy and cholecystectomy, showed feasibility; however, NOTES‐specific morbidity was introduced and this represents an important limitation. Conclusion NOTES experimentation in the preclinical setting has increased substantially. There has also been a significant increase in the application of NOTES in humans in the past decade. Enthusiasm for NOTES should be tempered by the risk of incurring NOTES‐specific morbidity. Surgeons should carefully consider patient preferences regarding this new minimally invasive option, as opinions are not unanimously supportive of NOTES. As technical limitations are overcome, the clinical application of NOTES is predicted to increase. It is paramount that, when this complex technique is performed on humans, it is applied judiciously by appropriately trained experts with outcomes recorded in a registry.